Neurotrophic Properties of Silexan, an Essential Oil from the Flowers of Lavender-Preclinical Evidence for Antidepressant-Like Properties - Friedland, Kristina; Silani, Giacomo; Schuwald, Anita; Stockburger, Carola; Koch, Egon; Nöldner, Michael; Müller, Walter E. (Pharmacopsychiatry, 2020)
Background Silexan, a special essential oil from flowering tops of lavandula angustifolia, is used to treat subsyndromal anxiety disorders. In a recent clinical trial, Silexan also showed antidepressant effects in patients suffering from mixed anxiety-depression (ICD-10 F41.2). Since preclinical data explaining antidepressant properties of Silexan are missing, we decided to investigate if Silexan also shows antidepressant-like effects in vitro as well as in vivo models.Methods We used the forced swimming test (FST) in rats as a simple behavioral test indicative of antidepressant activity in vivo. As environmental events and other risk factors contribute to depression through converging molecular and cellular mechanisms that disrupt neuronal function and morphology—resulting in dysfunction of the circuitry that is essential for mood regulation and cognitive function—we investigated the neurotrophic properties of Silexan in neuronal cell lines and primary hippocampal neurons.Results The antidepressant activity of Silexan (30 mg/kg BW) in the FST was comparable to the tricyclic antidepressant imipramine (20 mg/kg BW) after 9-day treatment. Silexan triggered neurite outgrowth and synaptogenesis in 2 different neuronal cell models and led to a significant increase in synaptogenesis in primary hippocampal neurons. Silexan led to a significant phosphorylation of protein kinase A and subsequent CREB phosphorylation.Conclusion Taken together, Silexan demonstrates antidepressant-like effects in cellular as well as animal models for antidepressant activity. Therefore, our data provides preclinical evidence for the clinical antidepressant effects of Silexan in patients with mixed depression and anxiety.
Keywords: lavender; synaptic plasticity; CREB; antidepressant effects; neurite outgrowth